Case Report of a True Accessory Mandibular Condyle - an Exceptionally Rare Abnormality - Siddika, Ayesha; Ferdousi, AM (Delta Medical College Journal, 2016)
Mandibular accessory condyle is rare. Literature search found most of the accessory condyles to arise from the mandibular coronoid process due to hyperactivity of attached temporalis muscle. Although neoplastic growth at mandibular coronoid mimicking an accessory condyle also been cited. Absence of report in recent publications regarding accessory mandibular condyle arising from the main mandibular condyle makes this anomali extremely rare. The present case report is about a true accessory mandibular condyle which caused the patient facial and occlusal disharmony. A 3D computerized tomographic imaging ascertained the exact location of the accessory condyle, its origin and resting position of the accessory and the main condylar head. The facial and occlusal disharmony settled completely within a short postoperative time following surgical intervention and mild elastic traction. Delta Med Col J. Jan 2016 4(1): 45-50